Isolation and characterization from novel actinobacteria and myxobacteria especially from marine habitats - Landwehr, Wiebke (2017)
This thesis is divided into 5 parts. The first part is dedicated to the isolation of marine myxobacteria from the “Marine Myxobacteria Cluster” (MMC). Therefore surface sediment was sampled from the Wadden Sea from northern Germany, the specific sequence for marine myxobacteria (MMC) was detected via specific PCR and diverse isolation approaches were started. Finally, 12 halotolerant Myxococcus strains were isolated which were closely related to terrestrial strains and do not harbour the MMC sequence. From these strains no new bioactive secondary metabolites could be detected. Two parts focus on the taxonomical analysis as well as the screening for novel bioactive secondary metabolites from marine actinobacteria. These were isolated from living marine sponges or sediment from Guam and the rhizosphere sediment from mangrove plants from India. Taxonomically, strains ICN19 and 21 seemed to present a new species. For the screening of novel secondary metabolites a new multi resistant test panel could be established, consisting of Gram - positive and -negative bacteria as well as fungi including same multi resistant clinical relevant strains like methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus faecium (VREF) and different antibiotic resistant E .coli strains. Rakicidins A, B and E as well as the anthraqiunones aloesaponarin II and 5-hydroxyaloesaponarin II were isolated. All five compounds exhibited bioactivity against Gram-positive bacteria, including the MRSA and VREF strains, which was never described before. Furthermore, 5-hydroxyaloesaponarin II was described to be produced by a bacterial wild type strain for the first time. Moreover the bioactive compound staurosporine was isolated from the marine Streptomyces strain ICN21. Out of deep sea samples from the North Atlantic Ocean 4 marine Streptomyces strains were isolated. Using 16S rRNA PCR, MALDI-TOF, RiboPrinter® and DNA-DNA analyses as well as physiological and morphological approaches, the strain ASO4 wet was described as ...